2020
DOI: 10.1016/j.exger.2019.110769
|View full text |Cite
|
Sign up to set email alerts
|

17α-Estradiol promotes ovarian aging in growth hormone receptor knockout mice, but not wild-type littermates

Abstract: Growth hormone receptor knockout mice (GHRKO) have reduced body size and increased insulin sensitivity. These mice are known for having extended lifespan, healthspan and female reproductive longevity. Seventeen α-estradiol (17α-E2) is reported to increase insulin sensitivity and extend lifespan in male mice, with less robust effects in female mice. The aim of this study was to evaluate the ovarian reserve in wild type and GHRKO mice treated with 17α-E2. The mice were divided into four groups, GHRKO mice receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
12
2
Order By: Relevance
“…As discussed throughout this review, most drugs that contribute to a longer life span also result in a slower exhaustion of ovarian reserve. Interestingly, 17α-E2 appears to have no effect on the ovarian reserve of normal mice, while in the long-lived GHRKO mice, it decreased the number of primordial follicles (52). These results are interesting and show that drugs proven to be more effective in males, have no effect in the ovarian aging of females.…”
Section: Other Life-extending Therapiesmentioning
confidence: 88%
See 1 more Smart Citation
“…As discussed throughout this review, most drugs that contribute to a longer life span also result in a slower exhaustion of ovarian reserve. Interestingly, 17α-E2 appears to have no effect on the ovarian reserve of normal mice, while in the long-lived GHRKO mice, it decreased the number of primordial follicles (52). These results are interesting and show that drugs proven to be more effective in males, have no effect in the ovarian aging of females.…”
Section: Other Life-extending Therapiesmentioning
confidence: 88%
“…In addition, the treatment with exogenous GH for a short period increased primordial follicle activation and reduced the ovarian reserve in df/ df and normal mice (26). Similar to df/df mice, GHRKO mice have a larger ovarian reserve than normal mice (52,53) and the treatment of GHRKO mice with IGF-I decreased the primordial follicle reserve (53). bGH mice, otherwise, had accelerated ovarian aging and a decreased ovarian primordial follicle reserve (26).…”
Section: Growth Hormonementioning
confidence: 97%
“…Estrogen receptors are key receptors to maintain ovarian granulosa cell differentiation, follicle and oocyte growth and development, and ovulation function. The abnormal functions of estrogen, its receptors, and estradiol synthesis-related enzymes (aromatase) are closely related to ovarian aging and infertility ( Isola et al., 2020 ). Also, the number of antral follicles selected for dominance and ovulation is largely dependent on the regulatory action and the density of FSHR and LHR on the granulosa cell surface ( Cai et al., 2007 ; Regan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression of Amh and Gdf9 and Bmp15 suggests higher ovarian reserve, and the increase of Amh and Gdf9 indicates the further preservation of follicular reserve after PMA treatment. A more recent study has also shown that GHRKO mice have twice the number of primordial follicles at 6 months of age compared with N mice (Isola et al, 2020) (Isola et al, 2020) The df/df, dw/dw and GHRKO mice all have GH-deficient characteristics (either during GH production or via the actions of GHR), and they showed extended ovarian lifespan at a cost of reduced fertility, while transgenic mice overexpressing GH have smaller ovarian reserves.…”
Section: Ghrko Micementioning
confidence: 99%